A MECHANISTIC MODEL FOR CALCITE CRYSTAL GROWTH USING SURFACE SPECIATION - I. A CLASSICAL CHEMICAL DESCRIPTION FOR STRONG ELECTROLYTE SOLUTIONS - Nilsson O.; Sternbeck J. (My University, 1999)
A new mechanistic model for the crystal growth kinetics of calcite is presented, accounting for the presence of various surface complexes. Calcite crystal growth rates were determined with the constant composition method at Ωc (calcite supersaturation) values of 1.5-9.8. In general the rate increases with Ωc, but variations in CO2 partial pressures and the (CO32-)/(Ca2+) ratio also have a major effect on the crystal growth rate. These effects are eliminated by assuming that calcite crystal growth proceeds through three reversible reactions, in which CaCO30(aq) and Ca2+(aq) are incorporated at specific surface complexes. The model derived rates closely follow the experimental rates over the entire experimental range (r = 0.996, n = 23). The obtained rate constants indicate that CaCO30(aq) is ~20 times more reactive than Ca2+(aq) at the calcite-water interface. This agrees with the fact that dehydration of metal ions precedes crystal growth and, in analogy with other metal-ligand complexes, the CO32- ligand will increase the rate of water exchange of Ca. This model is a modified version of a rhodochrosite crystal growth model (Sternbeck, 1997) which allows for the comparison of reaction mechanisms and rate constants. The rate constants for incorporation of CaCO30(aq) at the mineral surface are 55 to 270 times higher than for MnCO30(aq). This difference can not likely be explained by the water exchange rates, but may be due to the fact that ligand exchange mechanisms for Ca and Mn differ.